Ontology and School Culture: Does Legislation Influence School Culture in Centralized Education Systems? - Karampelas, Konstantinos; Kouroutsidou, Maria; Raptis, Nikolaos (International Journal of Learning, Teaching and Educational Research, 2018)
This study aims to identify linkage between the concepts of educational ontology, school culture and educational legislation. The first has to do with the basic fundamental elements of the educational system. The second has to do with the school climate and general working conditions. The third has to do with the laws abiding the system. All these complex concepts are relevant to the educational functions. However, their relationship and the way they interact have not been studied thoroughly. This study researches that relationship. The context of the research is the education system of Greece, which is recognized as being highly centralized. Through an examination of educational legal documents, the study draws a relationship linking, the three concepts in such systems. By examining the content of 435 legal documents, it concludes that their focus ontology-wise was mostly on the level of application of teaching work, instead of ideas or structures. This detailed structured implementation of school function leads to this centralized culture. https://doi.org/10.26803/ijlter.17.9.7